Effect of Different Priming Agents on Germination and Early Seedling Growth of Maize (Zea mays L.) in Khairahani, Chitwan - Idrishi, Mohammad Yunush; Gaire, Achyut (Agronomy Journal of Nepal, 2025)
Maize (Zea mays L.) is a second most important staple crop in Nepal, yet its productivity remains below potential due to poor seed quality and low germination. Seed priming is a simple and cost-effective approach to improve germination, seedling vigor, and crop establishment. A laboratory experiment was conducted in January 2025 at Rampur Campus, Chitwan, using a Completely Randomized Design (CRD) with three replications and nine treatments: hydro-priming (24 hrs), NaCl (1%), urea (0.5% and 1%), KNO₃ (1% and 2%), GA₃ (50 ppm and 75 ppm), and control, to evaluate their effects on maize germination and early seedling growth under controlled conditions. Seeds were soaked for 24 hrs, dried for 12 hrs, and germinated in Petri plates at 25 ± 2°C. Observations were recorded at 12-hour intervals on different germination parameters of seed. Results showed that GA₃ 75 ppm and urea 1% were the most effective treatments, achieving the highest germination percentage (75.19% and 74.63%), seedling vigor index (5717.14 and 4583.23), germination energy (76 both), germination index (13.76 and 13.78), radicle length (59.39 and 47.53 mm), plumule length (7.66 and 6.65 mm), and radicle to plumule ratio (7.78 and 7.34), followed by Hydro-priming and NaCl 1%. In contrast, control seeds showed the lowest values across all traits.  Early germination (12-36 hours) showed significant improvement, whereas later stages were non-significant. Overall, seed priming markedly enhanced germination, seedling vigor, and early growth. Among the tested treatments, GA₃ at 75 ppm and urea at 1% emerged as the most effective priming agents for enhancing germination and early seedling growth of maize.